IMPLEMENTATION OF BALANCED SCORECARD IN IMPROVING COMPANY PERFORMANCE AT PT. ROYAL PERMATA INDAH - Ramdan, Deden (Program Studi Ilmu Administrasi Bisnis FISIP UNPAS, 2023)
This study aims to identify and analyze the implementation of the balanced scorecard in improving company performance at PT. Royal Permata Indah. The results of the research carried out are expected to be considered in designing a balanced scorecard-based performance measurement system for companies. So that the management and company members can translate the company's vision, mission and strategy into measurable and well-planned actions. The research method used is descriptive qualitative analysis. The data collection used is interviews using interviews accompanied by observation techniques and literature. Data analysis techniques using interactive model analysis consist of data collection, data reduction, data presentation and drawing conclusions.